2018
DOI: 10.3847/1538-4357/aae70c
|View full text |Cite
|
Sign up to set email alerts
|

Astrochemical Kinetic Grid Models of Groups of Observed Molecular Abundances: Taurus Molecular Cloud 1 (TMC-1)

Abstract: The emission line spectra of cyanoacetylene and methanol reveal chemical and physical heterogeneity on very small (< 0.1 pc) scales toward the peak in cyanopolyyne emission in the Taurus Molecular Cloud, TMC-1 (CP). We generate grids of homogeneous chemical models using a three-phase rate equation approach to obtain all time-dependent abundances spanning the physical conditions determined from molecular tracers of compact and extended regions of emission along this line of sight. Each time-dependent abundance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…In addition, the neutralization rates are reduced significantly in low-metallicity regions where the dust-to-gas mass ratio is small, and in dense cores where coagulation leads to a large mean grain radius 5 . Maffucci et al (2018) In a paper devoted to cyanopolyynes and other oxygenated complex organic molecules in TMC1, Maffucci et al (2018) mention oscillatory solutions for their time-dependent model. Unfortunately, the authors do not extend their calculations further than two millions years.…”
Section: Grain Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the neutralization rates are reduced significantly in low-metallicity regions where the dust-to-gas mass ratio is small, and in dense cores where coagulation leads to a large mean grain radius 5 . Maffucci et al (2018) In a paper devoted to cyanopolyynes and other oxygenated complex organic molecules in TMC1, Maffucci et al (2018) mention oscillatory solutions for their time-dependent model. Unfortunately, the authors do not extend their calculations further than two millions years.…”
Section: Grain Chemistrymentioning
confidence: 99%
“…This is rather surprising, as such a behavior is a normal feature of nonlinear sets of chemical equations (see Gray & Scott 1994) and results probably from the limited range of integration time and parameter values considered in the current time-dependent chemical studies applied to interstellar clouds (Wakelam et al 2015). Various time dependent behaviors including oscillations are explicitly quoted in Maffucci et al (2018). This paper will be discussed below, as we believe their study to be not fully complete.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) and other volatile species can be readily used as markers of the evolutionary stage of interstellar medium (ISM) objects such as molecular clouds and regions of star formation. Similarly, a more sophisticated analysis of the evolutionary stage of ISM objects could include measurements of complex organic molecules (COMs) since the synthesis of COMs can vary both qualitatively and quantitatively upon the physical characteristics and evolutionary stage of each astrophysical object, as demonstrated by several observational, theoretical, and laboratory studies (Bergantini et al 2018;Maffucci et al 2018;Shingledecker et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gratier et al (2016) released a revised compilation of reference values for observed molecular abundances towards TMC-1 (CP) based on a Bayesian statistical method to account for outlier points in the original data of Ohishi et al (1992) and Ohishi & Kaifu (1998). Maffucci et al (2018) then investigated the effects on standard astrochemical models when their derived abundances were evaluated against these new values and explored the effects on their models when Eley-Rideal and van der Waals processes were considered as well. Thus far, the traditional approach for astrochemical models has been to assume that the formation of H 2 occurs on a single, arbitrary grain type.…”
Section: Tmc-1mentioning
confidence: 99%